Novel Peptide Vaccine GV1001 Rescues Hearing in Kanamycin/Furosemide-Treated Mice - Kim, Shin Hye; Jung, Gaon; Kim, Sangjae; Koo, Ja-Won (Frontiers in Cellular Neuroscience, 2018)
The cell-penetrating peptide GV1001 has been investigated as an anticancer agent and recently demonstrated anti-oxidant and anti-inflammatory effects. It has shown a protective effect on a kanamycin (KM)-induced ototoxicity mouse model. In the present study, we administered GV1001 at different time points after inducing hair cell damage, and examined if it rescues hair cell loss and restores hearing. A deaf mouse model was created by intraperitoneal injection of KM and furosemide. Firstly, to test the early temporal change of hearing and extent of hair cell damage after KM and furosemide injection, hearing and outer hair cells (OHCs) morphology were evaluated on day 1, day 2, and day 3 after injection. In the second experiment, following KM and furosemide injection, GV1001, dexamethasone, or saline were given for 3 consecutive days at different time points: D0 group (days 0, 1, and 2), D1 group (days 1, 2, and 3), D3 group (days 3, 4, and 5), and D7 group (days 7, 8, and 9). The hearing thresholds were measured at 8, 16, and 32 kHz before ototoxic insult, and 7 days and 14 days after KM and furosemide injection. After 14 days, each turn of the cochlea was imaged to evaluate OHCs damage. GV1001-treated mice showed significantly less hearing loss and OHCs damage than the saline control group in the D0, D1, and D3 groups (p<0.0167). However, there was no hearing restoration or intact hair cell in the D7 group. GV1001 protected against cochlear hair cell damage, and furthermore, delayed administration of GV1001 up to 3 days rescued hair cell damage and hearing loss in KM/furosemide-induced deaf mouse model.